Synthesis and Characterization of Major Green Tea Catechin Nanoparticle - Ashok Kumar*, S.; Suresh, M.; Kishore Kumar, S.N.; Kalaiselvi, P. (Asian Journal of Chemistry, 2013)
Epigallocatechin-3-gallate (EGCG), a principal polyphenol, which is most abundant and active component in green tea which has wide therapeutic effects against various diseases. However, EGCG used in clinical application has some downsides due to its low bioavailability and half-life. Hence increasing the bioavailability of EGCG without losing its potential therapeutic effects is of great challenge. In this study, we have prepared EGCG-loaded chitosan nanoparticles by ionic gelation method using sodium tripolyphosphate as ionic cross linking agent. The size, surface morphology, drug entrapment efficiency, drug releasing property and free radical scavenging activity of EGCG nanoparticle has been studied. The size of nanoparticle as determined by SEM ranged from 88-399 nm. FTIR results confirmed the drug entrapment in nanoparticles. The antioxidant property of nano-particulated EGCG and drug releasing assay showed sustained release of EGCG in the acid medium, which helps in increasing bioavailability of drug. Moreover the antioxidant activity of the drug was not found to be hindered by conversion into nanoparticles. However, further in vivo studies are warranted to explicate its therapeutic efficacy.